Analisis Terhadap Tindak Pidana Penipuan Dalam Kasus Arisan Online (Studi Putusan Pengadilan Negeri Binjai No.375/PID.SUS/2021/PN BNJ) - Lidya Ruth Panjaitan; Alvi Syahrin; Edi Yunara; Marlina Marlina (Jurnal Pencerah Bangsa, 2023)
Criminal acts of fraud in the management of online arisan (rotating savings) in their handling have caused many polemics or legal issues. Which limitation, it is necessary to have clarity regarding the concept of default which is the realm of civil law and fraud which is the realm of criminal law. To examine more deeply the regulation of criminal acts of online arisan fraud and proof of criminal offence of online arisan fraud according to Indonesian laws and regulations, as well as the judge’s legal considerations in ruling number 375/Pid.Sus/2021/PN Bnj against criminal acts of online arisan fraud. The research uses a normative juridical approach method, namely doctrinal legal research that refers to legal norms, which are statutory laws in Indonesia, so this research emphasizes secondary material sources, both in the form of regulations and theories law. Based on the research results, the regulation of criminal acts of fraud in online gatherings according to Indonesian laws and regulations is regulated in Article 28 paragraph (1) jo. Article 45 A paragraph (1) Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions.